Kajian teoritis penggunaan art therapy dalam pelaksanaan layanan bimbingan dan konseling di SMK - Isna Ni’matus Sholihah (Ikatan Bimbingan dan Konseling Sekolah)
Guidance and counseling programs are an integral part of schooling. Guidance and counseling in SMK is expected to facilitate the development of identity (identity) of students as a unique person and able to develop optimally in self-reliance. The complexity and diversity of problems faced by learners / counselors required that guidance and counseling / counselor teachers are able to provide prompt, precise services. Creativity and innovation are needed because counseling service is a combination of science and art. Art Therapy is one alternative that can be used as a solution for methods in the counseling process provided to learners. Art Therapy can be done with a variety of methods of painting or drawing, dancing, playing music instrument or singing, poetry and drama.